Effects of Anodal tDCS Stimulation in Predictable and Unpredictable Task Switching Performance: The Possible Involvement of the Parietal Cortex. (1st July 2022) - Wang, Ziyu; Kong, Ziye; Li, Chenlin; Liang, Jimin; You, Xuqun
Highlights: The current study investigates the a-tDCS induced effects over the parietal cortex. a-tDCS can decrease the predictable but not unpredictable task-switching performance. The parietal cortex is more likely to be involved in the proactive cognitive processes. Abstract: Transcranial direct current stimulation (tDCS) has been used to explore the causal relationship between specific brain regions and task switching. However, most studies have focused on the frontal cortex, and only few have examined other related cortices, e.g., the parietal cortex. So far, no prior study has systematically explored the tDCS-induced effect of the parietal cortex in different task switching types. Therefore, the current study mainly used the unilateral anodal-tDCS (a-tDCS) stimulation setting to investigate the possible involvement of the parietal cortex in predictable and unpredictable task switching. It was noted that compared with sham group, significantly higher switch cost reaction time of right anode tDCS (RA) group was found in predictable task but not unpredictable task. No interaction effect was observed between congruence and tDCS groups in predictable task. These findings suggested that a-tDCS over right parietal cortex could markedly decrease the predictable task-switching performance in both congruent and incongruent trials, and indicated that parietal cortex is more likely to be involved in the proactive cognitive processes, such as endogenous preparation.